1993
DOI: 10.1056/nejm199306173282403
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Aerosolized Tobramycin in Patients with Cystic Fibrosis

Abstract: The short-term aerosol administration of a high dose of tobramycin in patients with clinically stable cystic fibrosis is an efficacious and safe treatment for endobronchial infection with P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
216
0
13

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 429 publications
(235 citation statements)
references
References 27 publications
6
216
0
13
Order By: Relevance
“…9 Experimental and clinical data support the delivery of antibiotics to the respiratory tract. 25,[27][28][29][30] In addition, there is evidence that direct pulmonary exposure to aminoglycosides protects lung epithelial cells against http://www.pediatrics.org/cgi/content/full/100/5/e5oxidant injury. 31 Aerolized aminoglycosides have yielded inconsistent yet encouraging results for patients with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Experimental and clinical data support the delivery of antibiotics to the respiratory tract. 25,[27][28][29][30] In addition, there is evidence that direct pulmonary exposure to aminoglycosides protects lung epithelial cells against http://www.pediatrics.org/cgi/content/full/100/5/e5oxidant injury. 31 Aerolized aminoglycosides have yielded inconsistent yet encouraging results for patients with cystic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…31 Aerolized aminoglycosides have yielded inconsistent yet encouraging results for patients with cystic fibrosis. 29 Ramsey et al 30 have shown safety and efficacy with short-term administration of aerosolized tobramycin in stable cystic fibrosis patients using 1800 mg/day, which can be up to 5 to 10 times the IV dose. A prevailing problem when evaluating the usefulness of aerosol therapy is the estimation of the dose of medication actually delivered to the patient's lungs, which depends on many variables including nebulizer type and output, particle size, and patient breathing pattern.…”
Section: Discussionmentioning
confidence: 99%
“…In the first large study demonstrating the efficacy of inhaled tobramycin in 72 CF patients [39], tobramycin was delivered to the lungs using an ultrasonic nebuliser (UltraNeb 99/100). In two other clinical trials performed later with 520 CF patients [40], TNS was delivered using the PARI LC PLUS nebuliser and the Pulmo-Aide compressor.…”
Section: Page 8 Of 30mentioning
confidence: 99%
“…Finally, in a smaller, placebo-controlled study, the PARI BOY ® jet nebuliser/compressor system was used [41]. It is of interest that the type of nebuliser used in the Phase III clinical trials [39,40] affected the choice of nebuliser in other studies with scope other than device testing [42][43][44].…”
Section: Page 8 Of 30mentioning
confidence: 99%
See 1 more Smart Citation